Sarana Dan Prasarana Belajar Dalam Mewujudkan Kebersihan Dan Keindahan Kampus UIN Sumatera Utara - Chuzaiman Batubara (Jurnal Penelitian Medan Agama, 2018)
This study aims to explore data and evaluate learning facilities and infrastructure on the campus of UIN North Sumatra. The study was conducted using a qualitative approach in terms of science, this study used a socio-religious approach. The analysis used is data reduction, data display and conclusion. The results of this study indicate that learning facilities and infrastructure on the campus of UIN North Sumatra need to get attention and improvement to be used for more conducive learning. Cleanliness and beauty in the facilities and infrastructure of North Sumatra UIN are still fairly minimal, both in terms of maintenance of facilities and infrastructure and preservation. The efforts of the new leadership are limited to the regulation optimization plan that regulates it. In the future efforts will be made to harmonize the rules that provide guidance for campus residents in maintaining learning facilities and infrastructure in order to realize the cleanliness and beauty of the campus